(untitled) (Journal of Educational Sciences, 2021)
The modern process of teaching physics requires the application of new methods, techniques and new ideas. The pedagogical experience used in teaching physics helps the future teacher to demonstrate knowledge about the principles and laws of pedagogy and education, apply them in real situations, tak- ing into account their capabilities and characteristics, and improve their abilities. The article reveals the importance of methods and techniques of pedagogical practice for application in physics lessons in the preparation of educated, qualified specialists in accordance with the requirements of modern society, their role in the formation of a future specialist. Students of the Faculty of Physics and Technology of Al-Farabi Kazakh National University, who will become future physics teachers, were interviewed in a Google form, which identifies the advantages of pedagogical methods used in teaching physics. According to the results of the survey, the attitude of physics students to the methods of pedagogy as future teachers was determined. During the lesson, we used the Miro app and the Google form, the Kahoot program. The lesson took into account the ef- fectiveness and benefits of these programs, as a result of which the efficiency, convenience of using digital resources for feedback from students and some difficulties encountered during online lessons were identified. With the current pandemic, these apps have become an indispensable distance learning opportunity. Key words: the discipline of physics, the method of teaching practice, the effectiveness of the dis- tance learning.